1968
DOI: 10.1088/0022-3727/1/6/301
|View full text |Cite
|
Sign up to set email alerts
|

The absorption and atomic number corrections in electron-probe X-ray microanalysis

Abstract: The Monte Carlo model for electron scattering described in an earlier paper has been used to calculate the absorption and back-scattering corrections met in electron-probe x-ray microanalysis. Although agreement with experimental data is on the whole good, the calculated values for the correction factors are not sufficiently accurate for general use. However, in the case of light element analysis where very high absorption corrections are needed, the corrections calculated from Monte Carlo data are the best av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…EDS analyses were performed with a JEOL JED-2200 system (X-ray takeoff angle 30°). Pressed compact pellets of each starting material reagent were used as standard samples for quantitative analysis and acquired raw X-ray intensity data were compensated by methods of Springer [9], Bishop [10] and Philibert [11]. Specific surface areas were measured by N 2 absorption using the BET method with a BEL Japan BELSORP-mini II.…”
Section: Introductionmentioning
confidence: 99%
“…EDS analyses were performed with a JEOL JED-2200 system (X-ray takeoff angle 30°). Pressed compact pellets of each starting material reagent were used as standard samples for quantitative analysis and acquired raw X-ray intensity data were compensated by methods of Springer [9], Bishop [10] and Philibert [11]. Specific surface areas were measured by N 2 absorption using the BET method with a BEL Japan BELSORP-mini II.…”
Section: Introductionmentioning
confidence: 99%
“…Electron trajectories have often been calculated by Monte Carlo simulation to explain various phenomena related to electron beams impinged into solid materials [10][11][12][13][14][15][16][17][18]. In this simulation, various scattering processes can be treated flexibly, and many phenomena in electron probe microanalysis (EPMA) and scanning electron microscopy (SEM), e.g., normal incidence of high-energy electrons, have been successfully reproduced [10][11][12][13][14][15][16][17][18].…”
Section: B Detail Of Calculationmentioning
confidence: 99%
“…In this simulation, various scattering processes can be treated flexibly, and many phenomena in electron probe microanalysis (EPMA) and scanning electron microscopy (SEM), e.g., normal incidence of high-energy electrons, have been successfully reproduced [10][11][12][13][14][15][16][17][18]. The author has shown that the Monte Carlo method is also very useful for understanding electron trajectories in RHEED.…”
Section: B Detail Of Calculationmentioning
confidence: 99%
“…How deep does the typical electron penetrate before returning to the surface? A number of experimental investigations have been reported in the literature for backscattering of electrons from solid targets with incident energies up to 5 keV [10][11][12][13][14][15][16][17]; the results of these investigations were found to show considerable inconsistencies among themselves. The theoretical treatment of this fundamental scattering process at low impact energies is complicated due to failure of the Born approximation and lack of a detailed knowledge of the atomic potentials.…”
Section: Introductionmentioning
confidence: 99%